Glass fiber reinforced thermoplastic polymer composition
By packaging and applying polypropylene sheath in the glass fiber-reinforced thermoplastic polymer composition, and using a specific impregnation agent, the problems of insufficient fiber dispersion and excessive release of volatile compounds are solved, and the effects of improving tensile properties and reducing white spots are achieved.
Patent Information
- Application Number
- CN202380061866.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-27
- Filing Date
- 2023-07-18
- Publication Date
- 2025-04-08
AI Technical Summary
The existing glass fiber reinforced thermoplastic polymer compositions may experience insufficient fiber dispersion in the products, resulting in white spots, and release of volatile compounds, affecting the mechanical properties and visual appearance.
Unwinding the continuous glass multi-fiber strands by packaging and applying a polypropylene sheath around them to form a sheathed continuous multi-fiber strand, using aromatic phosphates, polyphosphonates or poly(phosphonates-co-carbonates) as impregnation agents to improve fiber dispersion and reduce the release of volatile compounds.
The tensile properties and mechanical properties of the glass fiber reinforced thermoplastic polymer composition are improved, the number of white spots in the molded article is reduced, and the release of volatile compounds is reduced, achieving a good visual appearance and performance.
Smart Images

Figure BDA0005284591580000071
Abstract
Description
[0001] The present invention relates to glass fiber reinforced thermoplastic polymer compositions and methods of producing such compositions.
[0002] The glass fiber reinforced thermoplastic polymer composition can be made by a method comprising the steps of unwinding a continuous glass multifilament strand from a package and applying a sheath of polypropylene around the multifilament strand to form a sheathed continuous multifilament strand.
[0003] Such a method is known from the international application WO 2009 / 080281. This published patent application discloses a method for producing a long glass fiber reinforced thermoplastic polymer composition, the method comprising the steps of: i) unwinding at least one continuous glass multifilament strand from a package, ii) applying an impregnating agent to the at least one continuous glass multifilament strand to form an impregnated continuous multifilament strand, and iii) applying a sheath of a thermoplastic polymer around the impregnated continuous multifilament strand to form a sheathed continuous multifilament strand.
[0004] It is desirable that molded articles made from glass fiber reinforced thermoplastic polymer compositions have good mechanical properties, such as tensile properties. In addition, it is desirable that the articles release fewer volatile compounds. A good visual appearance is also desirable, such as an appearance with fewer white spots. White spots may occur due to insufficient dispersion of the fibers in the article.
[0005] It is an object of the present invention to provide a glass fiber reinforced thermoplastic polymer composition in which the above-mentioned and / or other needs are met.
[0006] Therefore, the present invention provides a glass fiber reinforced thermoplastic polymer composition comprising a sheathed continuous multifilament strand, the sheathed continuous multifilament strand comprising a core extending in a longitudinal direction and a polymer sheath closely surrounding the core,
[0007] wherein the core comprises an impregnated continuous multifilament strand comprising at least one continuous glass multifilament strand, wherein the at least one continuous glass multifilament strand is impregnated with an impregnating agent,
[0008] wherein the polymer sheath consists of a thermoplastic polymer composition comprising a thermoplastic polymer,
[0009] The impregnating agent comprises at least one of aromatic phosphate, polyphosphonate, and poly(phosphonate-co-carbonate).
[0010] The present invention also provides a method for producing a glass fiber reinforced thermoplastic polymer composition according to the present invention, wherein the sheathed continuous multifilament strand is prepared by the following sequential steps:
[0011] a) unwinding at least one continuous glass multifilament strand from a package,
[0012] b) applying an impregnating agent to at least one continuous glass multifilament strand to form an impregnated continuous multifilament strand, and
[0013] c) applying a sheath of a thermoplastic polymer composition around the impregnated continuous multifilament strand to form a sheathed continuous multifilament strand.
[0014] Details regarding steps a)-c) are described in WO 2009 / 080281 A1, which is hereby incorporated by reference.
[0015] The method for producing the glass fiber reinforced thermoplastic polymer composition according to the present invention may further comprise the following steps:
[0016] d) Cutting the sheathed continuous glass multifilament strand into pellets.
[0017] It has surprisingly been found that molded articles made from the glass fiber reinforced thermoplastic polymer composition according to the invention have good tensile properties and emit less volatile compounds.
[0018] Sheathed continuous multifilament strand
[0019] The glass fiber reinforced thermoplastic polymer composition according to the present invention can be in the form of a pellet, comprising or consisting of a sheathed continuous multifilament strand. The sheathed continuous multifilament strand comprises or consists of a core and a polymer sheath. The core has a generally cylindrical shape and comprises an impregnated continuous multifilament strand containing glass filaments. The core is closely surrounded by a polymer sheath that is generally tubular and consists of a thermoplastic polymer composition around its circumference. The glass filaments have a length that is substantially equal to the axial length of the pellet.
[0020] The core is substantially free of sheath material. The sheath is substantially free of glass filaments. This pellet structure may be obtained by a wire coating process such as disclosed in WO2009 / 080281 and is distinct from pellet structures obtained via a typical pultrusion type process such as disclosed in US 6,291,064.
[0021] Preferably, the polymer sheath is substantially free of glass filaments, meaning that it comprises less than 2 wt. % of glass filaments, based on the total weight of the polymer sheath.
[0022] Preferably, the core has a radius of 800-4000 microns, and / or the polymer sheath has a thickness of 500-1500 microns.
[0023] Preferably, the core occupies 35-60% of the cross-sectional area of the pellet and the sheath occupies 40-65% of the cross-sectional area of the pellet.
[0024] Preferably, the amount of the impregnated continuous multifilament strand is 10-70 wt %, such as 15-60 wt %, 20-50 wt % or 25-45 wt % relative to the sheathed continuous multifilament strand. Preferably, the amount of the thermoplastic composition is 30-90 wt %, such as 40-85 wt %, 50-80 wt % or 55-75 wt % relative to the sheathed continuous multifilament strand. Preferably, the total amount of the impregnated continuous multifilament strand and the thermoplastic composition is 100 wt % relative to the sheathed continuous multifilament strand.
[0025] Polymer sheath
[0026] The sheath closely surrounds the core. The term "closely surrounding" as used herein is understood to mean that the polymer sheath substantially completely contacts the core. In other words, the sheath is applied to the core in such a way that there is no intentional gap between the inner surface of the sheath and the core containing the impregnated continuous multifilament strands. Nevertheless, it will be appreciated by the skilled person that certain small gaps may be formed between the polymer sheath and the core due to process variations.
[0027] The polymer sheath is composed of a thermoplastic polymer composition.
[0028] Thermoplastic polymer composition of polymer sheath
[0029] The thermoplastic polymer composition comprises a thermoplastic polymer. Preferably, the thermoplastic polymer composition consists of a thermoplastic polymer and additives as described below.
[0030] Thermoplastic polymers in the thermoplastic polymer composition of the polymer sheath
[0031] The amount of thermoplastic polymer can be at least 50 wt%, such as 50-99.9 wt%, 75-99.9 wt%, or 95-99 wt%, relative to the thermoplastic polymer composition.
[0032] Suitable examples of thermoplastic polymers include, but are not limited to, polyamides such as polyamide 6, polyamide 66, or polyamide 46; polyolefins, for example polypropylene and polyethylene; polyesters such as polyethylene terephthalate, polybutylene terephthalate; polycarbonates; polyphenylene sulfide; polyurethanes, and mixtures thereof.
[0033] The thermoplastic polymer is preferably a polyolefin, more preferably a polyolefin selected from polypropylene or an elastomer of ethylene and an α-olefin comonomer having 4 to 8 carbon atoms, and any mixtures thereof.
[0034] In one embodiment, preferably the thermoplastic polymer composition comprises at least 80% by weight of thermoplastic polymer, such as at least 90% by weight, at least 93% by weight, at least 95% by weight, at least 97% by weight, at least 98% by weight or at least 99% by weight of thermoplastic polymer, based on the thermoplastic polymer composition. In a specific embodiment, the thermoplastic polymer composition consists of a thermoplastic polymer. In another embodiment, the thermoplastic polymer composition comprises at least 60% by weight, such as at least 70% by weight, such as at least 75% by weight and / or at most 99% by weight, such as at most 95% by weight, such as at most 90% by weight of thermoplastic polymer.
[0035] Preferably, the thermoplastic polymer has a melt flow index measured according to ISO 1133-1:2011 (2.16 kg / 230°C) of 20-150 dg / min, such as 30-140 dg / min. Preferably, the thermoplastic polymer has a melt flow index measured according to ISO 1133-1:2011 (2.16 kg / 230°C) of 50-130 dg / min.
[0036] The polypropylene can be, for example, a propylene homopolymer or a random propylene copolymer or a heterophasic propylene copolymer.
[0037] Propylene homopolymers can be obtained by polymerizing propylene under suitable polymerization conditions. Propylene copolymers can be obtained by copolymerizing propylene and one or more other α-olefins, preferably ethylene, under suitable polymerization conditions. The preparation of propylene homopolymers and copolymers is described, for example, in Moore, EP (1996) Polypropylene Handbook. Polymerization, Characterization, Properties, Processing, Applications, Hanser Publishers: New York.
[0038] The random propylene copolymer may contain ethylene or an α-olefin as a comonomer, the α-olefin being selected from α-olefins having 4 to 10 C-atoms, preferably ethylene, 1-butene, 1-hexene or any mixture thereof. The amount of the comonomer is preferably up to 10 wt.-%, based on the random propylene copolymer, for example 2 to 7 wt.-%, based on the random propylene copolymer.
[0039] The polypropylene can be produced by any known polymerization technique and using any known polymerization catalyst system. As regards the techniques, mention may be made of slurry, solution or gas phase polymerization; as regards the catalyst systems, mention may be made of Ziegler-Natta, metallocene or single site catalyst systems. All are known per se in the art.
[0040] Heterophasic propylene copolymers are generally prepared in one or more reactors by polymerizing propylene in the presence of a catalyst and subsequently polymerizing an ethylene-α-olefin mixture. The resulting polymer material is heterophasic, but the specific morphology usually depends on the preparation method and the ratio of the monomers used.
[0041] The heterophasic propylene copolymer can be produced using any conventional technique known to the skilled person, for example a multistage process polymerization, such as bulk polymerization, gas phase polymerization, slurry polymerization, solution polymerization or any combination thereof. Any conventional catalyst system can be used, for example Ziegler-Natta or metallocene. Such techniques and catalysts are described, for example, in WO06 / 010414; Polypropylene and other Polyolefins, Ser van der Ven, Studies in Polymer Science 7, Elsevier, 1990; WO06 / 010414, US4399054 and US4472524.
[0042] Preferably, the heterophasic propylene copolymer is produced using a Ziegler-Natta catalyst.
[0043] The heterophasic propylene copolymer can be prepared by a process comprising the following steps:
[0044] - polymerizing propylene and optionally ethylene and / or α-olefins in the presence of a catalyst system to obtain a propylene-based substrate, and
[0045] - Subsequently polymerizing ethylene and α-olefins in a propylene-based matrix in the presence of a catalyst system to obtain dispersed ethylene-α-olefin copolymers. These steps are preferably carried out in different reactors. The catalyst systems of the first and second steps may be different or identical.
[0046] The heterophasic propylene copolymer of the composition of the present invention consists of a propylene-based matrix and a dispersed ethylene-α-olefin copolymer. The propylene-based matrix typically forms the continuous phase in the heterophasic propylene copolymer. The amount of the propylene-based matrix and the dispersed ethylene-α-olefin copolymer can be determined by 13 C-NMR determination, as is well known in the art.
[0047] The propylene-based matrix consists of a propylene homopolymer and / or a propylene copolymer consisting of at least 70 wt% of propylene monomer units and up to 30 wt% of comonomer units selected from ethylene monomer units and α-olefin monomer units having 4 to 10 carbon atoms, such as at least 80 wt% of propylene monomer units and up to 20 wt% of comonomer units, at least 90 wt% of propylene monomer units and up to 10 wt% of comonomer units, or at least 95 wt% of propylene monomer units and up to 5 wt% of comonomer units, based on the total weight of the propylene-based matrix.
[0048] Preferably, the comonomer in the propylene copolymer of the propylene based matrix is selected from ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene and 1-octene, and is preferably ethylene.
[0049] Preferably, the propylene based matrix consists of a propylene homopolymer.
[0050] The melt flow index (MFI) of the propylene based matrix (before mixing the heterophasic propylene copolymer into the composition of the present invention) (MFI PP ) can be, for example, at least 0.1 dg / min, at least 0.2 dg / min, at least 0.3 dg / min, at least 0.5 dg / min, at least 1 dg / min, at least 1.5 dg / min, and / or, for example, at most 50 dg / min, at most 40 dg / min, at most 30 dg / min, at most 25 dg / min, at most 20 dg / min, measured according to ISO 1133 (2.16 kg / 230°C). MFI PP It may be, for example, 0.1-50 dg / min, such as 0.2-40 dg / min, such as 0.3-30 dg / min, such as 0.5-25 dg / min, such as 1-20 dg / min, such as 1.5-10 dg / min, measured according to ISO 1133 (2.16 kg / 230°C).
[0051] The propylene-based matrix may for example be present in an amount of 50-95 wt%. Preferably, the propylene-based matrix is present in an amount of 60-85 wt%, such as at least 65 wt% or at least 70 wt% and / or at most 78 wt%, based on the total heterophasic propylene copolymer.
[0052] The propylene-based matrix is preferably semi-crystalline, i.e. it is not 100% amorphous, nor 100% crystalline. For example, the propylene-based matrix is at least 40% crystalline, such as at least 50%, such as at least 60% crystalline and / or such as up to 80% crystalline, such as up to 70% crystalline. For example, the propylene-based matrix has a crystallinity of 60 to 70%. For the purposes of the present invention, the crystallinity of the propylene-based matrix is measured according to ISO 11357-1 and ISO 11357-3 of 1997 using differential scanning calorimetry (DSC), using a scan rate of 10°C / min, a sample of 5 mg, and the second heating curve using 207.1 J / g as a theoretical standard for 100% crystalline material.
[0053] In addition to the propylene-based matrix, the heterophasic propylene copolymer also includes dispersed ethylene-alpha-olefin copolymers. Dispersed ethylene-alpha-olefin copolymers are also referred to as "dispersed phase" in this article. Dispersed phase embeds the heterophasic propylene copolymer in a discontinuous form. The particle size of the dispersed phase is generally in the range of 0.05 to 2.0 microns, as can be measured by transmission electron microscopy (TEM). The amount of the dispersed ethylene-alpha-olefin copolymers in the heterophasic propylene copolymer can sometimes be referred to as RC in this article.
[0054] The amount of ethylene monomer units in the ethylene-α-olefin copolymer may be from 20 to 65 wt%.The amount of ethylene monomer units in the ethylene-α-olefin copolymer dispersed in the heterophasic propylene copolymer may sometimes be referred to herein as RCC2.
[0055] The α-olefin in the ethylene-α-olefin copolymer is preferably selected from the group of α-olefins with 3-8 carbon atoms. Examples of suitable α-olefins with 3-8 carbon atoms include, but are not limited to, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene and 1-octene. More preferably, the α-olefin in the ethylene-α-olefin copolymer is selected from the group of α-olefins with 3 to 4 carbon atoms and any mixture thereof, more preferably the α-olefin is propylene, in which case the ethylene-α-olefin copolymer is an ethylene-propylene copolymer.
[0056] The MFI of the dispersed ethylene α-olefin copolymer (before mixing the heterophasic propylene copolymer into the composition of the present invention) (MFI rubber) can be, for example, at least 0.001 dg / min, at least 0.01 dg / min, at least 0.1 dg / min, at least 0.3 dg / min, at least 0.7 dg / min, at least 1 dg / min, and / or, for example, at most 30 dg / min, at most 20 dg / min, at most 15 dg / min, at most 10 dg / min, at most 5 dg / min or at most 3 dg / min. The MFI rubber can be, for example, 0.001-30 dg / min, such as 0.01-20 dg / min, such as 0.1-15 dg / min, such as 0.3-10 dg / min, such as 0.7-5 dg / min, such as 1-3 dg / min. The MFI rubber is calculated according to the following formula:
[0057]
[0058] in,
[0059] MFI heterophasic is the MFI (dg / min) of the heterophasic propylene copolymer measured according to ISO 1133 (2.16 kg / 230°C),
[0060] MFI matrix is the MFI (dg / min) of a propylene-based matrix measured according to ISO 1133 (2.16 kg / 230° C.),
[0061] The matrix content is the fraction of the propylene-based matrix in the heterophasic propylene copolymer,
[0062] The rubber content is the fraction of dispersed ethylene-α-olefin copolymer in the heterophasic propylene copolymer. The sum of the matrix content and the rubber content is 1. For the avoidance of any doubt, Log in the formula means log 10 .
[0063] The dispersed ethylene-α-olefin copolymer is present in an amount of 50-5 wt.-% based on the total heterophasic propylene copolymer. Preferably, the dispersed ethylene-α-olefin copolymer is present in an amount of 40-15 wt.-% based on the total heterophasic propylene copolymer, for example, in an amount of at least 22 wt.-% and / or for example, in an amount of at most 35 wt.-% or at most 30 wt.-%.
[0064] In the heterophasic propylene copolymer in the composition of the present invention the sum of the total weight of the propylene based matrix and the total weight of the dispersed ethylene-α-olefin copolymer is 100 wt% of the heterophasic propylene copolymer.
[0065] The α-olefin in the ethylene-α-olefin copolymer is preferably selected from the group of α-olefins having 3-8 carbon atoms and any mixture thereof, preferably the α-olefin in the ethylene-α-olefin copolymer is selected from the group of α-olefins having 3-4 carbon atoms and any mixture thereof, more preferably the α-olefin is propylene, in which case the ethylene-α-olefin copolymer is an ethylene-propylene copolymer. Examples of suitable α-olefins having 3-8 carbon atoms that can be employed as ethylene comonomers to form ethylene α-olefin copolymers include, but are not limited to, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene and 1-octene.
[0066] Elastomers of ethylene and an α-olefin comonomer having 4 to 8 carbon atoms may, for example, have a molecular weight of 0.850 to 0.915 g / cm 3 These elastomers are sometimes called plastomers.
[0067] The α-olefin comonomer in the elastomer is preferably an acyclic monoolefin such as 1-butene, 1-pentene, 1-hexene, 1-octene or 4-methylpentene.
[0068] Thus, the elastomer is preferably selected from the group consisting of ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-1-octene copolymers and mixtures thereof, more preferably wherein the elastomer is selected from ethylene-1-octene copolymers. Most preferably, the elastomer is ethylene-1-octene copolymers.
[0069] Preferably, the density of the elastomer is at least 0.865 g / cm 3 and / or up to 0.910 g / cm 3 For example, the density of the elastomer is at least 0.850, such as at least 0.865, such as at least 0.88, such as at least 0.90 and / or such as at most 0.915, such as at most 0.910, such as at most 0.907, such as at most 0.906 g / cm 3 More preferably, the density of the elastomer is from 0.88 up to and including 0.907 g / cm 3 Most preferably, the density of the elastomer is from 0.90 to up to and including 0.906 g / cm 3 within the range.
[0070] Elastomers suitable for use in the present invention are commercially available, for example, from Exxon Chemical Company of Houston, Texas, under the trademark EXACT TM ENGAGE TMThe polymers are commercially available from MITSUI Chemicals Group of Tokyo, Minato, under the trademark TAFMER TM Nexlene TM Purchased.
[0071] Elastomers can be prepared using methods known in the art, such as by using a single-site catalyst, i.e., a catalyst in which the transition metal component is an organometallic compound and in which at least one ligand has a cyclopentadienyl anionic structure, which is bonded and coordinated to the transition metal cation through the anionic structure. This type of catalyst is also known as a "metallocene" catalyst. Metallocene catalysts are described, for example, in U.S. Patent Nos. 5,017,714 and 5,324,820. Elastomers can also be prepared using conventional types of heterogeneous multisite Ziegler-Natta catalysts.
[0072] Preferably, the elastomer has a melt flow index of 0.1-40 dg / min (ISO 1133, 2.16 kg, 190° C.), such as at least 1 dg / min and / or at most 35 dg / min. More preferably, the elastomer has a melt flow index of at least 1.5 dg / min, such as at least 2 dg / min, such as at least 2.5 dg / min, such as at least 3 dg / min, more preferably at least 5 dg / min and / or preferably at most 30 dg / min, more preferably at most 20 dg / min, more preferably at most 10 dg / min, measured according to ISO 1133 using a 2.16 kg weight and at a temperature of 190° C.
[0073] Preferably, the amount of ethylene incorporated into the elastomer is at least 50 mol%. More preferably, the amount of ethylene incorporated into the elastomer is at least 57 mol%, such as at least 60 mol%, at least 65 mol%, or at least 70 mol%. Even more preferably, the amount of ethylene incorporated into the elastomer is at least 75 mol%. The amount of ethylene incorporated into the elastomer can generally be up to 97.5 mol%, such as up to 95 mol% or up to 90 mol%.
[0074] In some preferred embodiments, the thermoplastic polymer in the thermoplastic polymer composition is a mixture of a propylene homopolymer and a heterophasic propylene copolymer.
[0075] Additives for thermoplastic polymer compositions of polymer sheaths
[0076] The thermoplastic polymer composition of polymer sheath can contain other conventional additives, for example nucleating agent and clarifying agent, stabilizer, filler, plasticizer, antioxidant, lubricant, antistatic agent, antiscratch agent, impact modifier, acid scavenger, circulation additive, coupling agent, antimicrobial agent, antifogging additive, smooth additive, anti-blocking additive, polymer processing aid, fire retardant, coloring agent and the like.This type of additive is well known in the art.Technician will understand how to select the type and amount of additive so that they can not adversely affect the target property.The amount of additive can be for example the 0.1-50 % by weight of thermoplastic polymer composition, for example 0.1-25 % by weight or 1.0-5.0 % by weight.
[0077] In some preferred embodiments, the additives in the thermoplastic polymer composition of the polymer sheath comprise a coupling agent.
[0078] Suitable examples of coupling agents include functionalized polyolefins grafted with acid or anhydride functional groups. Polyolefins are preferably polyethylene or polypropylene, more preferably polypropylene. Polypropylene can be a propylene homopolymer or a propylene copolymer. Propylene copolymers can be composed of at least 70% by weight of propylene and up to 30% by weight of alpha-olefins, such as ethylene, based on the total weight of a propylene-based matrix, for example, composed of at least 80% by weight of propylene and up to 20% by weight of alpha-olefins, for example, composed of at least 90% by weight of propylene and up to 10% by weight of alpha-olefins. Preferably, the alpha-olefin in the propylene-alpha-olefin copolymer is selected from alpha-olefins having 2 or 4-10 carbon atoms, and is preferably ethylene. Examples of acid or anhydride functional groups include (meth) acrylic acid and maleic anhydride. Particularly suitable materials are, for example, maleic acid functionalized propylene homopolymers (e.g., Exxelor PO1020 supplied by Exxon).
[0079] The amount of the coupling agent may be, for example, 0.5 to 3.0 wt%, preferably 1.0 to 2.0 wt%, based on the sheathed continuous multifilament strand.
[0080] core
[0081] The sheathed continuous multifilament strand comprises a core extending in a longitudinal direction. The core comprises an impregnated continuous multifilament strand comprising at least one continuous glass multifilament strand, wherein the at least one continuous glass multifilament strand is impregnated with an impregnating agent. The impregnated continuous multifilament strand is prepared from the continuous glass multifilament strand and the impregnating agent.
[0082] Preferably, at least one impregnated continuous multifilament strand forms at least 90 wt. %, more preferably at least 93 wt. %, even more preferably at least 95 wt. %, even more preferably at least 97 wt. %, even more preferably at least 98 wt. %, for example at least 99 wt. % of the core. In a preferred embodiment, the core consists of at least one impregnated continuous multifilament strand.
[0083] In the context of the present invention, 'extending in the longitudinal direction' means 'oriented in the direction of the major axis of the sheathed continuous multifilament strand'.
[0084] Core with sheath continuous multi-filament strand glass filament
[0085] Continuous multifilament strands contain glass filaments. Glass fibers are generally supplied as multiple continuous, very long filaments and in the form of strands, rovings, or yarns. A filament is a single fiber of a reinforcing material. A strand is a bundle of multiple filaments. A yarn is a collection of strands, such as strands twisted together. A roving refers to a collection of strands wound into a package.
[0086] For purposes of the present invention, a glass multifilament strand is defined as a plurality of bundled glass filaments.
[0087] Glass multifilament strands and their preparation are known in the art.
[0088] The filament density of the continuous glass multifilament strand can vary within wide limits. For example, the continuous glass multifilament strand can have a density of 1000-10000 g / 1000 m.
[0089] Preferably, the continuous glass multifilament strand has a density of 1000-2900 g / 1000 m, more preferably 1500-2800 g / 1000 m.
[0090] The continuous glass multifilament strand may have a filament diameter of 5-50 μm, more preferably 10-30 μm, even more preferably 15-25 μm. Typically the glass filaments are circular in cross section, meaning that the thickness as defined above will refer to the diameter. The glass filaments are generally circular in cross section.
[0091] Preferably, the ratio between the length of the glass fibers and the diameter of the glass fibers in the pellets (L / D ratio) is 500-1000.
[0092] The length of the glass filaments is in principle not limited, since it is substantially equal to the length of the sheathed continuous multifilament strand. However, for practical reasons of being able to handle the strands, it may be necessary to cut the sheathed continuous multifilament strand into shorter strands. For example, the length of the sheathed continuous multifilament strand is at least 1 m, such as at least 10 m, such as at least 50 m, such as at least 100 m, such as at least 250 m, such as at least 500 m and / or such as at most 25 km, such as at most 10 km.
[0093] Preferably, the glass multifilament strand is coated with a sizing composition (i.e., coating) to improve adhesion to the polymer matrix. The sizing composition can be arranged on substantially all glass filaments or on a portion of glass filaments in the thermoplastic composition. Sizing provides coated glass filaments, which can be bonding or non-bonding to the thermoplastic polymer composition of the sheath. Preferably, the coated glass filaments are bonded to the polyester in the thermoplastic polymer composition of the sheath.
[0094] The sizing composition may include polyepoxides, poly(meth)acrylates, polyarylene ethers, polyurethanes, or combinations thereof. The polyepoxides may be phenolic epoxy resins, epoxidized carboxylic acid derivatives (e.g., reaction products of esters of polycarboxylic acids having one or more unesterified carboxyl groups and compounds comprising more than one epoxy group), epoxidized diene polymers, epoxidized polyolefin polymers, or combinations thereof.
[0095] The sizing composition may also include a silane coupling agent to promote bonding with the glass fiber. The silane coupling agent may be tri(C 1-6 Alkoxy)monoaminosilane, tri(C 1-6 Alkoxy)diaminosilane, tri(C 1-6 Alkoxy) (C 1-6 Alkylureido)silane, tri(C 1-6 Alkoxy) (epoxy C 1-6 Alkyl)silane, tri(C 1-6 Alkoxy) (glycidyloxy C 1-6 Alkyl)silane, tri(C 1-6 Alkoxy) (thiol C 1-6 The silane coupling agent is preferably (3-aminopropyl)triethoxysilane, (3-glycidyloxypropyl)trimethoxysilane, (2-(3,4-epoxycyclohexyl)ethyl)triethoxysilane, (3-mercaptopropyl)trimethoxysilane, (3-(2-aminoethylamino)propyl)triethoxysilane, (3-ureidopropyl)triethoxysilane, or a combination thereof. Preferably, the silane coupling agent is aminopropyltriethoxysilane, glycidylpropyltrimethoxysilane, or a combination thereof.
[0096] Other materials that may be included in the sizing composition include, but are not limited to, antistatic agents, coupling agents, lubricants, wetting agents, or the like.
[0097] The sizing composition can be present in an amount of 0.1 to 5 wt % based on the weight of at least one continuous glass multifilament strand. The sizing composition can be applied to glass fiber by any means, such as soaking the glass multifilament strand in the sizing composition, or contacting the glass multifilament strand with an aqueous emulsion or suspension of the sizing composition. Other coating methods include using an aqueous dispersion of the sizing composition, which is applied to uncoated glass multifilament strands with a roller in a continuous manner, which can be a heat treatment or curing step afterwards.
[0098] Typically, after the sizing composition is applied to the glass filaments, the filaments are bundled into a continuous glass multi-filament strand and then wound onto a spool to form a package.
[0099] Preferably, the amount of the at least one continuous glass multifilament strand is 10-70 wt%, such as 15-60 wt%, 20-50 wt% or 25-45 wt%, relative to the sheathed continuous multifilament strand.
[0100] Impregnation agent
[0101] The impregnated continuous multifilament strand is prepared from a continuous glass multifilament strand and an impregnating agent, and specifically by applying the impregnating agent to the continuous glass multifilament strand preferably in an amount of 0.50-18.0 wt % relative to the sheathed continuous multifilament strand.
[0102] According to the present invention, the impregnating agent comprises at least one of aromatic phosphate, polyphosphonate, and poly(phosphonate-co-carbonate).
[0103] Preferably, the impregnating agent comprises an aromatic phosphate ester.
[0104] Preferably, the aromatic phosphate is selected from:
[0105] Resorcinol bis(diphenyl phosphate);
[0106] Tetraphenylresorcinol bis(diphenyl phosphate);
[0107] Bisphenol A bis(diphenyl phosphate);
[0108] Bisphenol A diphosphate;
[0109] Resorcinol bis(di-2,6-ditolyl phosphate);
[0110] Phosphoric acid, mixed esters with [1,1'-biphenyl]-4-4'-diol and phenol;
[0111] Phosphorus oxychloride, polymer with 1,3-benzenediol, phenyl ester;
[0112] 1,3-phenylene-tetrakis(2,6-dimethylphenyl)diphosphate;
[0113] Isopropenylphenyl diphenyl phosphate;
[0114] 4-Phenylphenol formaldehyde phosphonic acid phenyl ester;
[0115] Tris(2,6-dimethylphenyl)phosphate;
[0116] Resorcinol bis(di-2,6-ditolyl phosphate);
[0117] Bisphenol S bis(diphenyl phosphate); and
[0118] Resorcinol-bisphenol A phenyl phosphate, and
[0119] A combination of them.
[0120] Most preferably, the aromatic phosphate is bisphenol A bis(diphenyl phosphate).
[0121] Preferably, the amount of the impregnating agent is 1.0-10.0 wt %, more preferably 1.5-5.0 wt %, more preferably 2.5-5.0 wt % relative to the sheathed continuous multifilament strand.
[0122] Preferably, the amount of the impregnating agent or aromatic phosphate is 1.0-10.0 wt. %, more preferably 1.5-5.0 wt. %, more preferably 2.5-5.0 wt. % relative to the sheathed continuous multifilament strand. This results in a particularly low number of white spots.
[0123] For example, the weight ratio of the impregnating agent or aromatic phosphate ester to the continuous glass multifilament strand is 1:4-1:30, preferably 1:5-1:20, and more preferably 1:6-1:13.
[0124] The impregnating agent may also contain other types of compounds. Preferably, the total amount of aromatic phosphates, polyphosphonates, poly(phosphonate-co-carbonates) relative to the impregnating agent is at least 80 wt%, such as at least 90 wt%, at least 93 wt%, at least 95 wt%, at least 97 wt%, at least 98 wt% or at least 99 wt%.
[0125] Preferably, the total amount of aromatic phosphate relative to the impregnant is at least 80 wt%, such as at least 90 wt%, at least 93 wt%, at least 95 wt%, at least 97 wt%, at least 98 wt% or at least 99 wt%. In some embodiments, the impregnant consists of aromatic phosphate.
[0126] The impregnating agent may comprise a microcrystalline wax, for example as described in detail in WO 2015 / 062825, page 5, line 17 to page 7, line 9, incorporated herein by reference. In this respect it is to be understood that the microcrystalline wax may be a single microcrystalline wax or a blend of several microcrystalline waxes.
[0127] Any method known in the art can be used to apply the liquid impregnant to the continuous glass multifilament strand. The application of the liquid impregnant can be carried out using a die. Other suitable methods for applying the impregnant to the continuous multifilament strand include a coater with a belt, a roller and a hot melt coater. Such methods are described, for example, in documents EP0921919B1, EP0994978B1, EP0397505B1, WO2014 / 053590A1 and the references cited therein. The method used should enable a constant amount of impregnant to be applied to the continuous multifilament strand.
[0128] Preferably, the amount of the impregnated continuous multifilament strand is 15-75 wt %, such as 20-65 wt %, 25-55 wt % or 30-50 wt % relative to the sheathed continuous multifilament strand. Preferably, the total amount of the impregnated continuous multifilament strand and the polymer sheath is 100 wt % relative to the sheathed continuous multifilament strand.
[0129] Other aspects
[0130] The present invention provides pellets comprising or consisting of the glass-fiber-reinforced thermoplastic polymer composition according to the present invention.
[0131] The pellets may typically have a length of 2-50 mm, preferably 5-30 mm, more preferably 6-20 and most preferably 10-16 mm. The length of the glass fibers is typically about the same as the length of the pellets.
[0132] The total amount of thermoplastic polymer composition and impregnated continuous multifilament strands in the pellets is preferably at least 95%, at least 98%, at least 99%, at least 99.9% or 100% by weight relative to the pellets.
[0133] The granules according to the invention are preferably prepared by a process comprising the following sequential steps:
[0134] a) unwinding at least one continuous glass multifilament strand from a package,
[0135] b) applying an impregnating agent to at least one continuous glass multifilament strand to form an impregnated continuous multifilament strand, and
[0136] c) applying a sheath of a thermoplastic polymer composition around the impregnated continuous multifilament strand to form a sheathed continuous multifilament strand, and
[0137] d) Cutting the sheathed continuous glass multifilament strand into pellets.
[0138] Step d) may be followed by a step of molding the pellets into a (semi)finished product. Suitable examples of molding methods include injection molding, compression molding, extrusion and extrusion molding. Injection molding is widely used to produce articles such as automotive exterior parts such as bumpers and tailgates, automotive interior parts such as instrument panels, or automotive parts under the hood. Housings for electronic products and electrical appliances can also be manufactured by injection molding. Extrusion is widely used to produce articles such as rods, sheets and tubes. The article may have a wall thickness of, for example, 0.1-10 mm.
[0139] Therefore, the present invention further relates to a molded article comprising the glass fiber reinforced thermoplastic polymer composition or pellets according to the present invention, wherein the article is selected from automotive exterior parts such as bumpers and tailgates, automotive interior parts such as instrument panels, automotive parts under the hood and housings for electronic products and appliances.
[0140] The present invention further relates to a process for producing a molded article by molding the glass fiber reinforced thermoplastic polymer composition or pellets according to the present invention, wherein the article is selected from automotive exterior parts such as bumpers and tailgates, automotive interior parts such as instrument panels, automotive parts under the hood and housings for electronic products and appliances.
[0141] The present invention also relates to the use of at least one of aromatic phosphates, polyphosphonates, poly(phosphonate-co-carbonates) as an impregnating agent for preparing a glass fiber reinforced thermoplastic polymer composition comprising a sheathed continuous multifilament strand, the sheathed continuous multifilament strand comprising a core extending in the longitudinal direction and a polymer sheath tightly surrounding the core,
[0142] wherein the core comprises an impregnated continuous multifilament strand comprising at least one continuous glass multifilament strand, wherein the at least one continuous glass multifilament strand is impregnated with an impregnating agent,
[0143] The polymer sheath is composed of a thermoplastic polymer composition comprising a thermoplastic polymer.
[0144] It is noted that the present invention relates to the subject matter defined by the independent claims alone or in combination with any possible combination of features described herein, preferably in particular those combinations of features presented in the claims. Thus, it is to be understood that all combinations of features relating to the composition according to the invention, all combinations of features relating to the method according to the invention, as well as all combinations of features relating to the composition according to the invention and of features relating to the method according to the invention are described herein.
[0145] It is further noted that the terms 'comprising', 'including', 'containing' do not exclude the presence of other elements. However, it is also understood that the description of a product / composition comprising certain components also discloses a product / composition consisting of these components. A product / composition consisting of these components may be advantageous because it provides a simpler and more economical method for preparing the product / composition. Similarly, it is also understood that the description of a method comprising certain steps also discloses a method consisting of these steps. A method consisting of these steps may be advantageous because it provides a simpler and more economical method.
[0146] The present invention is now illustrated with the aid of the following examples, but the invention is not limited thereto. Example
[0147] Materials used
[0148] PP1: Braskem F1000HC2, polypropylene homopolymer with the following properties: density 905kg / m 3 , the melt flow index is 120 dg / min at 230°C and 2.16 kg (test method: ISO1133), and the melting point is 160-175°C.
[0149] PP2: SABIC PP595A, propylene homopolymer with the following properties: Density 905 kg / m 3 , melt flow index is 45 dg / min at 230°C and 2.16 kg (test method: ISO1133), melting point: 160-175°C.
[0150] Coupling agent 1: Exxelor PO1020 powder (PP-g-MA) from ExxonMobil, density 900 kg / m 3 , melting point 162°C, melt flow index 430 dg / min at 230°C and 2.16 kg (test method: ASTM D1238).
[0151] GF: a glass roving having a diameter of 19 micrometers and a tex of 3000 (tex means grams of glass per 1000 meters), which comprises a sizing composition containing a silane coupling agent.
[0152] Impregnating agent 1: Wax, commercially available as IGI Paraflex 4838A.
[0153] Impregnating agent 2: ADEKA FP-600 bisphenol A bis(diphenyl phosphate), with a viscosity higher than 10000 mPa.s at 23°C and 50-200 mPa.s at 80°C as measured according to ASTM D445.
[0154] AO1076: Antioxidant 1076, from BASF
[0155] AOB225: Antioxidant B225, from BASF
[0156] UV119: UV stabilizer UV119, from SABO SpA
[0157] UV770: UV stabilizer UV770, from BASF
[0158] CMB: Masterbatch, from Ampacet
[0159] Preparation of sheathed continuous multifilament strands (wire coating)
[0160] Sheathed continuous multifilament strands were prepared using a wire coating process as described in detail in the Examples of WO 2009 / 080281 A1 using the components given in Table 1 .
[0161] Impregnating agent 1 or 2 was applied to the GF to obtain an impregnated continuous glass multifilament strand.
[0162] The polypropylene, coupling agent and other additives shown in Table 1 are fed to the extruder, and the impregnated continuous glass multifilament strand is sheathed using an extruder head wire coating die. The sheathing step is performed directly online after the impregnation step. The obtained sheathed continuous multifilament strand is cut into pellets with a length of 8-15 mm and a diameter of 3-4 mm. The obtained pellets are molded using an ARBURG 320T injection molding machine to prepare samples for testing.
[0163] The following properties were measured and are shown in Table 1.
[0164] Ash content was tested according to ISO 3451 at 800°C for 30 minutes.
[0165] White spots (WS) were observed on 510 x 310 x 2 mm molded parts at room temperature. Table 1 shows the average number of white spots observed on 20 molded parts.
[0166] Charpy notched impact was tested according to ISO 179 after aging for 7 days at 23°C.
[0167] Flexural properties were tested according to ISO 178 after aging for 7 days at 23°C.
[0168] Tensile properties were tested according to ISO 527 after aging for 7 days at 23°C.
[0169] The FOG value was determined according to VDA 278.
[0170] Table 1
[0171] CEx 1 CEx 2 Ex 3 CEx 4 Ex 5 PP1 weight% 54.84 54.84 52.84 52.84 PP2 weight% 52.84 Impregnation agent 1 weight% 4 2 4 Impregnation agent 2 weight% 2 4 GF weight% 40.2 40.2 40.2 40.2 40.2 AO 1076 weight% 0.2 0.2 0.2 0.2 0.2 AO B225 weight% 0.2 0.2 0.2 0.2 0.2 Coupling agent weight% 2 2 2 2 2 UV 119 weight% 0.06 0.06 0.06 0.06 0.06 UV 770 weight% 0.2 0.2 0.2 0.2 0.2 CMB weight% 0.3 0.3 0.3 0.3 0.3 total weight% 100.00 100.00 100.00 100.00 100.00 Visual WS Count 3.4 >25 >25 1.9 1.1 Ash content % 39.94 40.61 41.2 40.42 41.05 Charpy Shock <![CDATA[kJ / m 2 ]]> 20.05 19.78 20.28 19.93 20.34 Flexural modulus MPa 8404 9558 9574 8970 9348 Fracture flexural stress MPa 172.7 189.1 189.8 179.4 185.5 Flexural Strength MPa 182.2 201 198.5 188.6 194.5 Tensile modulus MPa 8773.7 9831 10242 9583.1 10066.6 Tensile Strength MPa 109.4 120.2 122.6 117.2 119.2 FOG μg / g 495 531 455 542 453
[0172] Comparison of CEx2 with Ex3 and comparison of CEx4 with Ex5 shows that the use of Impregnant 2 according to the invention results in higher tensile properties (tensile modulus and tensile strength) and lower FOG values than the use of Impregnant 1. Furthermore, the impact strength and flexural properties remain at similar levels between the use of Impregnant 1 and Impregnant 2.
[0173] Furthermore, comparison of Ex3 with Ex5 shows that higher amounts of Impregnant 2 resulted in significantly lower numbers of white spots.
Claims
1. A glass fiber reinforced thermoplastic polymer composition comprising a sheathed continuous multifilament strand comprising a core extending in a longitudinal direction and a polymer sheath closely surrounding the core, wherein the core comprises an impregnated continuous multifilament strand comprising at least one continuous glass multifilament strand, wherein the at least one continuous glass multifilament strand is impregnated with an impregnating agent, wherein the polymer sheath is composed of a thermoplastic polymer composition comprising a thermoplastic polymer, The impregnating agent comprises at least one of aromatic phosphate, polyphosphonate, and poly(phosphonate-co-carbonate).
2. The glass fiber reinforced thermoplastic polymer composition according to claim 1, wherein the impregnating agent comprises an aromatic phosphate ester.
3. The glass fiber reinforced thermoplastic polymer composition according to claim 2, wherein the aromatic phosphate ester is selected from: Resorcinol bis(diphenyl phosphate); Tetraphenylresorcinol bis(diphenyl phosphate); Bisphenol A bis(diphenyl phosphate); Bisphenol A diphosphate; Resorcinol bis(di-2,6-ditolyl phosphate); Phosphoric acid, mixed esters with [1,1'-biphenyl]-4-4'-diol and phenol; Phosphorus oxychloride, polymer with 1,3-benzenediol, phenyl ester; 1,3-phenylene-tetrakis(2,6-dimethylphenyl) diphosphate; Isopropenylphenyl diphenyl phosphate; 4-Phenylphenol formaldehyde phosphonic acid phenyl ester; Tris(2,6-dimethylphenyl)phosphate; Resorcinol bis(di-2,6-ditolyl phosphate); Bisphenol S bis(diphenyl phosphate); and Resorcinol-bisphenol A phenyl phosphate, and Their combination, Preferably, the aromatic phosphate ester is bisphenol A bis(diphenyl phosphate).
4. The glass fiber reinforced thermoplastic polymer composition according to any one of the preceding claims, wherein the amount of the impregnating agent or the aromatic phosphate ester is 1.5-5.0 wt% relative to the sheathed continuous multifilament strand.
5. The glass fiber reinforced thermoplastic polymer composition according to any one of the preceding claims, wherein the amount of the impregnating agent or the aromatic phosphate ester relative to the sheathed continuous multi-filament strand is 2.5-5.0 wt%.
6. A glass fiber reinforced thermoplastic polymer composition according to any one of the preceding claims, wherein the thermoplastic polymer has a melt flow index determined according to ISO 1133-1:2011 (2.16 kg / 230°C) of 20-150 dg / min, such as 30-140 dg / min.
7. The glass fiber reinforced thermoplastic polymer composition according to any one of the preceding claims, wherein the thermoplastic polymer has a melt flow index determined according to ISO 1133-1:2011 (2.16 kg / 230°C) of 50 to 130 dg / min.
8. A glass fiber reinforced thermoplastic polymer composition according to any of the preceding claims, wherein the amount of the thermoplastic polymer is at least 80 wt %, such as at least 90 wt %, at least 93 wt %, at least 95 wt %, at least 97 wt %, at least 98 wt % or at least 99 wt %, relative to the thermoplastic polymer composition.
9. The glass fiber reinforced thermoplastic polymer composition according to any one of the preceding claims, wherein the thermoplastic polymer is a polyolefin, preferably wherein the polyolefin is selected from polypropylene or an elastomer of ethylene and an α-olefin comonomer having 4 to 8 carbon atoms, and any mixture thereof.
10. The glass fiber reinforced thermoplastic polymer composition according to any one of the preceding claims, wherein the thermoplastic polymer composition of the polymer sheath comprises a maleic acid functionalized propylene homopolymer.
11. The glass fiber reinforced thermoplastic polymer composition according to any one of the preceding claims, wherein the amount of the impregnated continuous multifilament strand is 10-70 wt%, such as 15-60 wt%, 20-50 wt% or 25-45 wt% relative to the sheathed continuous multifilament strand.
12. Pellets comprising the glass fiber reinforced thermoplastic polymer composition according to any one of the preceding claims.
13. A method for preparing a glass fiber reinforced thermoplastic polymer composition according to any one of claims 1 to 11, comprising the following sequential steps: a) unwinding at least one continuous glass multifilament strand from a package, b) applying an impregnating agent to the at least one continuous glass multifilament strand to form an impregnated continuous multifilament strand, and c) applying a sheath of a thermoplastic polymer composition around the impregnated continuous multifilament strand to form a sheathed continuous multifilament strand, and Optionally, d) chopping the sheathed continuous glass multifilament strand into pellets.
14. A molded article comprising the glass fiber reinforced thermoplastic polymer composition according to any one of claims 1 to 11 or the pellets according to claim 12.
15. Use of an aromatic phosphate ester as an impregnating agent for preparing a glass fiber reinforced thermoplastic polymer composition comprising a sheathed continuous multifilament strand comprising a core extending in the longitudinal direction and a polymer sheath closely surrounding the core, wherein the core comprises an impregnated continuous multifilament strand comprising at least one continuous glass multifilament strand, wherein the at least one continuous glass multifilament strand is impregnated with an impregnating agent, The polymer sheath is composed of a thermoplastic polymer composition comprising a thermoplastic polymer.
Citation Information
Patent Citations
Method and apparatus for manufacturing fibre-reinforced material
EP0397505B1
Chemical treatments for fibers and wire-coated composite strands for molding fiber-reinforced thermoplastic composite articles
EP0921919B1
Nonaqueous sizing system for glass fibers and injection moldable polymers
EP0994978B1
Catalyst components and catalysts for the polymerization of alpha-olefins
US4399054A
Components and catalysts for the polymerization of olefins
US4472524A